REVERSE CULTURE SHOCK IN VIETNAMESE STUDENTS RETURNING FROM AMERICAN EDUCATION = Sốc ngược văn hóa ở các du học sinh Việt Nam sau khi về nước - Trần, Thị Thúy Hà (2020)
Little is known about the reverse culture shock in Vietnamese students who have lived and studied in America. Reverse culture shock may impact their process of integration into their home culture. This research investigated the reverse culture shock that Vietnamese students faced after their return to Vietnam. It also examined the correlation between the age of moving oversea, the time living oversea and the influence of reverse culture shock. In this study, qualitative research design was applied. This study used the method of purposive sampling to take the participants and employed content analysis to analyze the data. This research revealed several findings. First, the returnees experience reveres culture shock mostly in language, cuisine, working style and traffic culture. Secondly, the age at which the students move oversea negatively correlates with the influence of reverse culture shock, and there exists the positive correlation between the time of living oversea and the influence of reverse culture shock.